Pilihan Domisili Yurisdiksi Dalam Permohonan PKPU Berdasarkan Asas Lex Specialis Derogat Legi Generalis - Diana Ayu Mardiani; Muhammad Eko Prasetiyo; Nyulistiowati Suryanti; Deviana Yuanitasari (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
The parties can determine the content of the agreement, including regarding dispute resolution, which includes the choice of domicile jurisdiction agreed upon and binding for the parties. However, a conflict arises when the Commercial Court, which lacks authority, grants a PKPU petition due to the jurisdiction choice stipulated in the agreement. The research method used in this legal study is a normative juridical research method. The purpose is to understand the position of the Bankruptcy and PKPU Law with the clauses binding for the parties. The result of this research is that Law Number 37 of 2004 concerning Bankruptcy and PKPU is a lex specialis, so the law also does not provide a choice of law in bankruptcy and PKPU petitions. In PKPU cases, the Commercial Court is not subject to the choice of law and authority regulated in the agreement.